Role of NAD+ in regulating cellular and metabolic signaling pathways - Sara Amjad; Sabah Nisar; Ajaz A. Bhat; Ab Rauf Shah; Michael P. Frenneaux; Khalid Fakhro; Mohammad Haris; Ravinder Reddy; Zoltan Patay; Joseph Baur; Puneet Bagga (Elsevier, 2021)
Background: Nicotinamide adenine dinucleotide (NAD+), a critical coenzyme present in every living cell, is involved in a myriad of metabolic processes associated with cellular bioenergetics. For this reason, NAD+ is often studied in the context of aging, cancer, and neurodegenerative and metabolic disorders. Scope of review: Cellular NAD+ depletion is associated with compromised adaptive cellular stress responses, impaired neuronal plasticity, impaired DNA repair, and cellular senescence. Increasing evidence has shown the efficacy of boosting NAD+ levels using NAD+ precursors in various diseases. This review provides a comprehensive understanding into the role of NAD+ in aging and other pathologies and discusses potential therapeutic targets. Major conclusions: An alteration in the NAD+/NADH ratio or the NAD+ pool size can lead to derailment of the biological system and contribute to various neurodegenerative disorders, aging, and tumorigenesis. Due to the varied distribution of NAD+/NADH in different locations within cells, the direct role of impaired NAD+-dependent processes in humans remains unestablished. In this regard, longitudinal studies are needed to quantify NAD+ and its related metabolites. Future research should focus on measuring the fluxes through pathways associated with NAD+ synthesis and degradation.